2011
DOI: 10.1177/0363546511415655
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Graft Failure

Abstract: Autograft hamstrings and allografts had a significantly higher failure rate in the age group of patients 25 years and younger compared with the bone-patellar tendon-bone autograft. These data suggest that bone-patellar tendon-bone autografts may be a better graft source for young, active individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 22 publications
1
63
1
Order By: Relevance
“…Barrett et al 2 showed at a minimum 2-year follow-up that patients younger than 25 years (mean age, 18 years) had significantly increased failure rates regardless of graft type. Reported failure rates for patients younger than 25 years were 12% for patellar tendon autografts, 25% for hamstring tendon auto-grafts, and 29% for allografts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barrett et al 2 showed at a minimum 2-year follow-up that patients younger than 25 years (mean age, 18 years) had significantly increased failure rates regardless of graft type. Reported failure rates for patients younger than 25 years were 12% for patellar tendon autografts, 25% for hamstring tendon auto-grafts, and 29% for allografts.…”
Section: Discussionmentioning
confidence: 99%
“…This left a total of 21 comparative studies. Twelve of the 21 studies were excluded for not specifying whether the allografts had been irradiated (n = 6) 2,21,22,25,29,33 or including allografts that had been irradiated (n = 6). 6,11,26,36,37,39 The 9 remaining studies compared autograft and nonirradiated allograft tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Identifying an optimal rehabilitation protocol may help to decrease rates of ACL-R failure, estimated from 3–10%, and even higher among young patients and those who return to high activity levels [2, 8, 9]. In fact, in a retrospective analysis of 1131 consecutive ACL-Rs performed at one institution over seven years, ACL graft failure occurred in 16% of patients under age 25 compared to 8.3% of those older than 25 years [10]. …”
Section: Introductionmentioning
confidence: 99%
“…ACL tears are one of the most frequent forms of knee ligament injury with an estimated 150,000–200,000 ACL tears occurring annually in the United States alone12. ACL tears have critical implications for the physiological biomechanics of the tibiofemoral joint, often leading to functional instability, damage to meniscus and articular cartilage and an increased risk for PTOA51314.…”
mentioning
confidence: 99%